Arthur Asa Berger, Shop ‘Til You Drop: Consumer Behavior and American Culture - Palko, Kathy (Journal for the study of religion, nature and culture, 2006)
Arthur Asa Berger, Shop ‘Til You Drop: Consumer Behavior and American Culture (Lanham MD: Rowman & Littlefield, 2005), pp. 152. Paperback $20, £14.99, ISBN 0-7425-3691-2. Hardback $60, £46.00, ISBN 0-7425-3690-4.